2011
DOI: 10.1007/s11661-011-0844-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Aging on the Microstructure and Mechanical Behavior of Dual-Phase, Precipitation-Hardened, Powder Metallurgy Stainless Steels

Abstract: i ABSTRACT Increasing demand for high strength powder metallurgy (PM) steels has resulted in the development of dual phase PM steels. In this work, the effects of thermal aging on the microstructure and mechanical behavior of dual phase precipitation hardened powder metallurgy (PM) stainless steels of varying ferritemartensite content were examined. Quantitative analyses of the inherent porosity and phase fractions were conducted on the steels and no significant differences were noted with respect to aging tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It has been reported that the thermal aging embrittlement in CDSS was caused by the precipitation that formed in the ferrite phase after long-term thermal aging, e.g., the G-phase precipitates and the spinodal decomposition during which the ferrite phase decomposes into a Fe-rich α-phase and a Cr-rich α'-phase [10,11,[13][14][15]. Many researchers have found that the mechanical properties of CDSS are strongly dependent on the strength of each individual phase [16,17] and their microstructures, e.g., the volume fraction and the morphology of the ferrite phase, have meaningful influence on the fracture toughness, thermal aging embrittlement, high-temperature ductility, impact properties and corrosion resistance of duplex stainless steel [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the thermal aging embrittlement in CDSS was caused by the precipitation that formed in the ferrite phase after long-term thermal aging, e.g., the G-phase precipitates and the spinodal decomposition during which the ferrite phase decomposes into a Fe-rich α-phase and a Cr-rich α'-phase [10,11,[13][14][15]. Many researchers have found that the mechanical properties of CDSS are strongly dependent on the strength of each individual phase [16,17] and their microstructures, e.g., the volume fraction and the morphology of the ferrite phase, have meaningful influence on the fracture toughness, thermal aging embrittlement, high-temperature ductility, impact properties and corrosion resistance of duplex stainless steel [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Also, researchers found that at some point over-aging occurs at higher temperatures because the carbide precipitates coarsen and causes a decrease in strength. The ductility was also observed to increase slightly with aging due to tempering of the martensite [46].…”
Section: Surface Region Away From Main Crackingmentioning
confidence: 98%
“…During this process, the carbon diffuses out of the martensite, meaning that the distortion of the martensite phase is reduced and thus lowers the residual stresses and strength of the material. If precipitation hardening elements such as copper or aluminum are introduced into dual-phase steels, the opposite occurs and the material is actually strengthened with increasing thermal exposure [46].…”
Section: Thermal Agingmentioning
confidence: 99%
“…For the unaged duplex stainless steel, a higher content of ferrite can enhance the mechanical properties, while the impact energies of duplex stainless steel are found to decrease with the increasing ferrite content for the aged condition. Besides the effect of the microstructure, as a multi-phase material, the bulk mechanical properties of CDSS are also highly dependent on the mechanical properties of each individual phase [22,23]. Stewart [22] applied a conventional rule of mixtures approach to the stress-strain data obtained from microconstituents in a dual phase precipitation hardened (DPPH) steel to predict the bulk behavior.…”
Section: Introductionmentioning
confidence: 99%